Risk Factors for Cerebral Vasospasm in Patients with Aneurysmal Subarachnoid Hemorrhage: A Tertiary Care Center Experience - Khan, Muhammad Mohsin; Shaikh, Nissar; Yousaf, Zohaib; Sultan, Hussain; Sadek, George; Khan, Adnan; Kamran, Saadat; Ahmed, Ayman Z.; Albanna, Walid; Belkhair, Sirajeddin; Ayyad, Ali (Asian Journal of Neurosurgery, 2022)
Objectives Cerebral vasospasm in subarachnoid hemorrhage (SAH) is associated with high morbidity and mortality. There is a lack of consensus on the risk factors leading to cerebral vasospasm in patients with aneurysmal subarachnoid hemorrhage (aSAH). In this retrospective study, our objective was to determine the association of risk factors for cerebral vasospasm aSAH.Methods A total of 259 charts of aSAH patients consecutively admitted to the surgical intensive care unit of Hamad General Hospital from January 2007 to December 2016 were reviewed and included. The patient's demographic data, including comorbidities like hypertension (HTN), was recorded. Variables of interest included measurements of the neurological deficit on admission, the severity of SAH, treatment modality, and the initial computerized tomography scan of the head for intraventricular hemorrhage, intracerebral hemorrhage, or hydrocephalus. Multivariate analysis and multiple logistic regression analyzed the relationship to identify the association of independent variables.Results Out of the 259 patients, 34% (n = 87) suffered from cerebral vasospasm. The severity of SAH was associated with the development of cerebral vasospasm (p < 0.05). The presence of HTN and neurological deficits on admission were associated with an increased risk of cerebral vasospasm (p < 0.05, p < 0.01, respectively). Hydrocephalus requiring treatment using external ventricular drains decreased the risk of cerebral vasospasm (p < 0.05). Intraventricular and intracerebral hemorrhage were not associated with cerebral vasospasm (p = 0.25, p = 0.16). The endovascular treatment of cerebral aneurysms was associated with an increased risk of cerebral vasospasm (p < 0.05).Conclusion Cerebral vasospasm is common among patients admitted with aSAH. It is significantly associated with the history of HTN, the neurological deficit on admission that corelates more strongly to the motor deficit on admission, the severity of hemorrhage (modified Fischer score), and endovascular treatment. External ventricular drainage was associated with a decrease in cerebral vasospasm. The present study's findings shed light on cerebral vasospasm's risk factors in the country and the region.
Keywords: cerebral aneurysm; clinical vasospasm; delayed cerebral ischemia; subarachnoid hemorrhage; vasospasm